Pengaruh Penerapan Discovery Learning Dipadu Classroom Debate Terhadap Keterampilan Argumentasi Siswa - Anggraheni Dewi Salsabilla; Umi Fatmawati; Puguh Karyanto; Slamet Santosa (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Argumentation skills are essential competencies that students must master to meet 21st-century challenges. This research aims to analyze the effectiveness of discovery learning integrated with classroom debate in improving students' argumentation skills. The method used in this study is a pre-experiment method with a type of one group pretest-posttest design using one clases, namely classes X-1 and research subjects as many as 35 students. Data were collected through tests, observations, and documentation. Data analysis uses paired t-test to verify the data against the proposed hypothesis. The research results show that the average argumentation skills in discovery learning integrated with classroom debate is higher than before the treatment (pretest mean = 59.54; posttest mean = 72.71). The results of the analysis can be concluded that the implementation of discovery learning integrated with classroom debate effectively influences students' argumentation skills. Thus, this integrated model is recommended to be implemented to support argumentation skills development in high school.